Facilitating International Production Networks : The Role of Trade Logistics - Saslavsky, Daniel (World Bank, Washington, DC, 2013)
This paper shows that networked trade in parts and components is more sensitive to the importing country's logistics performance than is trade in final goods. In the baseline specification, the difference between the two trade semi-elasticities is around 45 percent, which suggests that the effect is quantitatively important. In addition, the analysis finds that logistics performance is particularly important for trade in the Asia-Pacific region, which is exactly where the emergence of international production networks has been most pronounced over recent years. The results suggest that policymakers can support the development of international production networks by helping improve trade logistics performance.